Characterization and chemical oxidation of Nanoclay filled low density Polyethylene (LDPE) composites: the effect of Poly (acrylic acid) - Hafizan Hassan (Universiti Malaysia Perlis, 2008)
The effects of poly(acrylic acid) (PAA) on the characterization and chemical oxidation of low density polyethylene (LDPE) and nanoclay were studied with a Differential scanning calorimetriy (DSC), Thermalgravimetry analysis (TGA), oxidation behavior and Scanning electron microscope (SEM), respectively. LDPE and Nanoclay were blend with different composition content with or without the addition of compatibilizer (PAA), were prepared with a Z-Blade Mixer at 180 ºC temperature and rotor speed of 50 rotor per minute (rpm). The mixed sample are then been compressed by using hydraulic hot press to form a sheet samples composites. It was found that the composition of 2.5 per hundred resin (phr) for LDPE/Nanoclay with or without addition of PAA show the optimum composition compare to the other composition. The range of glass transition temperature, melting temperature, percentage crystallinity and the temperature of 50 wt % show higher in properties and gave dramatically enhance compare to others composition. The percent crystallization of LDPE/Nanoclay composites was lower than pure LDPE but higher than LDPE/nanoclay with PAA composites. The interfacial properties between LDPE/Nanoclay were lacking with addition of PAA as evidenced by structure morphology revealed by SEM. Therefore LDPE/Nanoclay composites with higher clay loading show more chemical oxidation compare to LDPE/Nanoclay with PAA composites by oxidation behavior analysis.